2015
DOI: 10.3928/1081597x-20150727-01
|View full text |Cite
|
Sign up to set email alerts
|

Vector Analysis, Rotational Stability, and Visual Outcome After Implantation of a New Aspheric Toric IOL

Abstract: Implantation of the new Bi-Flex T IOL was a safe, stable, and effective method to correct preexisting regular corneal astigmatism during cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
7
13
0
Order By: Relevance
“…On the basis of the keratometric data, the predictability of the new combined procedure was evaluated. Alpin's method was used in the present study, as the method is able to comprehensively analyze the changes of astigmatism (17). In the present study, the SIA was closely correlated with the TIA.…”
Section: Post-mentioning
confidence: 59%
See 2 more Smart Citations
“…On the basis of the keratometric data, the predictability of the new combined procedure was evaluated. Alpin's method was used in the present study, as the method is able to comprehensively analyze the changes of astigmatism (17). In the present study, the SIA was closely correlated with the TIA.…”
Section: Post-mentioning
confidence: 59%
“…Vector analysis. Keratometric astigmatism vectors were evaluated using the Alpins method, which assesses the effective change in keratometric astigmatism (17). Vector parameters analyzed included: The target induced astigmatism (TIA), defined as the astigmatic correction in magnitude and axis the operator intended to induce, which is equivalent to the pre-operative astigmatism; surgically induced astigmatism (SIA), defined as the amount and axis of astigmatic change actually induced by surgery; difference vector (DV), defined as the vector difference of TIA and SIA and reflecting the post-operative astigmatism; angle of error (AE), which is the angle offset between SIA and TIA-it is positive if SIA is on an axis counterclockwise to TIA and negative if SIA is on an axis clockwise to TIA; magnitude of the error (ME), which is the magnitude difference between SIA and TIA-it is positive for overcorrection and negative for undercorrection; correction index, calculated by dividing the SIA by the TIA-it is ideally 1.0, and >1.0 for overcorrection and <1.0 for undercorrection; index of success (IOS), calculated by dividing the DV by the TIA-it is ideally 0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that 25% to 40% of cataract patients have astigmatism more than 1.0 diopters (D) [1,2]. With the increasing demands for good refractive outcomes after cataract surgery, toric intraocular lenses (IOLs) have been widely used to correct preoperative corneal astigmatism during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…6 Several studies have reported successful visual and refractive outcomes after implantation of different model soft toric IOL. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The purpose of the current study is to report our clinical and visual outcomes at 1 month after uncomplicated cataract surgery with toric IOL implantation (SupraPhob).…”
mentioning
confidence: 99%